1985
DOI: 10.1289/ehp.8560165
|View full text |Cite
|
Sign up to set email alerts
|

Effects of PCB exposure on biochemical and hematological findings in capacitor workers.

Abstract: Certain former operations in capacitor manufacturing resulted in extensive direct contact of the workers with electrical grade polychlorinated biphenyls (PCBs). A study group of 194 such individuals, all exposed to Aroclor 1016 and many previously exposed to Aroclors 1242 and/or 1254, was examined before (1976) and after (1979) discontinuance of PCB use in the operations (1977). At the two examinations, the approximate geometric mean serum levels (in ppb) and 5 to 95% ranges were for lower PCBs (LPCB), 363 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
2

Year Published

2000
2000
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(27 citation statements)
references
References 42 publications
(62 reference statements)
1
24
2
Order By: Relevance
“…The weights for each job then were multiplied by how long the participant worked in that job, and the results were summed over all jobs to estimate total cumulative occupational exposure to PCBs for each participant. Occupational exposure was also partitioned according to the years when specific Aroclors were used by GE, that is, 1946-1953for Aroclor 1254, 1953-1971for Aroclor 1242, and 1971-1977 for Aroclor 1016 (with minor Aroclor 1221 usage) (Lawton et al, 1985).…”
Section: Occupational Exposure To Pcbsmentioning
confidence: 99%
See 2 more Smart Citations
“…The weights for each job then were multiplied by how long the participant worked in that job, and the results were summed over all jobs to estimate total cumulative occupational exposure to PCBs for each participant. Occupational exposure was also partitioned according to the years when specific Aroclors were used by GE, that is, 1946-1953for Aroclor 1254, 1953-1971for Aroclor 1242, and 1971-1977 for Aroclor 1016 (with minor Aroclor 1221 usage) (Lawton et al, 1985).…”
Section: Occupational Exposure To Pcbsmentioning
confidence: 99%
“…Areas surrounding the plant had an average air PCB concentration of 6.2 mg/m 3 (Taylor et al, 1991), whereas ambient air concentrations in urban areas distant from the plants averaged 0.1 mg/m 3 (Kutz and Yang, 1975). Fischbein et al (1979) analyzed sera from 310 workers in these facilities in 1976 and found that they were, on average, 10-to 20-fold higher than in the general population (Wolff et al, 1982;Lawton et al, 1985). A subgroup of our cohort also had sera archived from 1976, allowing us to compare PCB concentrations and estimate their half-lives over a 28-year period.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fig. 1.9 shows ranges of air PCB concentrations in capacitor-manufacturing sites (Ouw et al, 1976;Bertazzi et al, 1982;Fischbein et al, 1982;Lawton et al, 1985;. The earlier concentrations (measured in the 1950s-1960s) were highest (Bertazzi et al, 1982), and decreased in later years.…”
Section: Capacitor Manufacturementioning
confidence: 99%
“…In addition, PCB exposure during prenatal and early life has been associated with incidence of infectious and allergic diseases in children, and alterations in immune-system development. Lawton et al (1985) tested 194 workers exposed occupationally (152 men, 42 women) to one or more of the Aroclors 1254, 1242, and 1016 in a capacitor plant factory for an average duration of 17 years. The results taken in 1976 were compared with those from the same workers taken in 1979, two years after discontinuation of all PCB use in 1977.…”
Section: (A) Adultsmentioning
confidence: 99%